Masson’s tumor of the thoracic spine: A rare cause of slowly progressive paraplegia - Kostić Andrija; Rančić Nemanja; Golubović Jelena; Pantić Milica (Vojnosanitetski Pregled, 2024)
Introduction. Intravascular papillary endothelial hyperplasia is an unusual reactive proliferation of endothelial cells around an organized thrombus, which occurs either in a dilated blood vessel, hematoma, or preexisting vascular lesion. These tumors rarely affect the central nervous system. Symptoms depend on the localization of the process itself. Localization in the central nervous system is limited to the intracranial space. Localization in the spinal canal is extremely rare, and only a few clinical cases have been described so far in the literature. Case report. A 67- year-old female patient was examined neurologically initially due to bilateral weakness of the lower extremities, accompanied by a feeling of pain and muscle tension, dominantly in the upper legs, more to the right. The complaints were present a year ago, and before that period, the patient was in a stable state of health. Due to a severe neurological deficit and the need for detailed exploration, the patient was hospitalized. A diagnosis was performed, which showed the localization of the pathological process in the thoracic 5–6 region of the spinal column. Decompression surgery was performed, and with the ex tempore findings metastasis was ruled out. Definitive pathohistological findings proved Masson’s tumor. After the operation, the neurological weakness recovered. Conclusion. Masson’s tumor, although rarely localized in spinal canal, is curable if it is correctly diagnosed and if an adequate therapeutic approach is applied. The initially presented symptoms may resemble numerous neurological or systemic diseases, which requires the clinician to be continuously aware of such rare pathological processes.